Assessment of smallholder farmers’ demand for and adoption constraints to small-scale irrigation technologies: Evidence from Ethiopia - Tesfaye, M. Z.; Balana, Bedru; Bizimana, J. (Elsevier, 2021)
Increasing agricultural productivity through irrigation technologies is recognized as an effective way to improve smallholders’ livelihoods and food security in developing countries. However, most smallholder farmers do not have access to irrigation technologies. Using a double-bounded contingent valuation survey data from smallholders in Ethiopia and probit and bivariate probit models, this paper analyzes smallholder farmers’ demand for agricultural water lifting technologies (WLTs) and the factors affecting the demand for these technologies. Assessment of farmers’ preferences among three water lifting technologies available in local markets (motorized pump, rope and washer and pulley) show that farmers prefer motorized pumps to pulley or rope and washer technologies. Use of motorized pumps is more efficient and save labour than pulley or rope and washer technologies. However, results show that smallholders are constrained by inadequate access to financing options to adopt more efficient and labour-saving water lifting technology and hence operate below the production possibility frontier. Enhanced access to finance could help ease this constraint and allow smallholders to acquire more efficient irrigation technologies, enhance adoption and improve productivity. With a growing population pressure and land fragmentation in rural Ethiopia, the livelihoods of smallholders depend mainly on the meagre land endowment they possess. Increasing the productivity of land using yield enhancing technologies, particularly multiple cropping per year via small-scale irrigation is key to improve their livelihoods. Targeted interventions are thus warranted to mitigate the key adoption constraints such as improving access to credit and technical know-how of smallholders.